2019
DOI: 10.1016/j.jad.2019.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging insights into the link between depression and Insomnia: A systematic review

Abstract: Background: Insomnia is a symptom of Major Depressive Disorder (MDD) and genome wide association studies pointed to their strong genetic association. Although the prevalence of insomnia symptoms in MDD is noticeable and evidence supports their strong bidirectional association, the number of available neuroimaging findings on patients with MDD with insomnia symptoms is limited. However, such neuroimaging studies could verily improve our understanding of their shared pathophysiology and advance corresponding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 122 publications
(172 reference statements)
0
42
0
1
Order By: Relevance
“…The amygdala plays a crucial role in processing and memorizing arousing and fear-inducing stimuli [ 30 , 31 ]. Moreover, it is discussed as an important link between insomnia and depression [ 8 •]. Given these facts, the region might be of particular interest in insomnia from a HT perspective.…”
Section: Neuroimaging Studies On the Amygdalamentioning
confidence: 99%
See 1 more Smart Citation
“…The amygdala plays a crucial role in processing and memorizing arousing and fear-inducing stimuli [ 30 , 31 ]. Moreover, it is discussed as an important link between insomnia and depression [ 8 •]. Given these facts, the region might be of particular interest in insomnia from a HT perspective.…”
Section: Neuroimaging Studies On the Amygdalamentioning
confidence: 99%
“…Moreover, demographic trends in these countries suggest that the societal relevance of insomnia might even increase in the future [ 4 ], given the fact that the prevalence rises with age [ 2 , 5 ]. Insomnia is also closely linked to depression, as epidemiological (insomnia as a predictor of depression, see [ 6 , 7 ]) and neurobiological (for a systematic review, see [ 8 •]) research suggests. It seems therefore particularly important to understand underlying features of insomnia related to mood and affect.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the pre-frontal areas, entorhinal cortex, parahippocampal gyrus, temporal gyrus, and thalamus contributed to PSQI prediction in both groups. These regions have been consistently found to be abnormal in insomnia patients compared to controls ( O'Byrne et al, 2014 , Zhou et al, 2017 , Wang et al, 2018 , Yan et al, 2018 , Bagherzadeh-Azbari et al, 2019 ). The entorhinal cortex, parahippocampal gyrus, and temporal gyrus may play a crucial role in long-term memory encoding ( Schon et al, 2016 , Newmark et al, 2013 , Park et al, 2011 ), while the pre-frontal area is critical for working memory ( D'Esposito and Postle, 2015 ) and the thalamus is related to sleep regulation ( Coulon et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, these patients showed lower spontaneous activity in regions of higher-order cognitive networks ( Li et al, 2016 ) and higher activity in sensory/perception-related regions ( Zhou et al, 2017 ). Considering the interaction between regions, several studies have demonstrated abnormalities in both local regional homogeneity ( Wang et al, 2016 ) and distributed functional connectivity among regions spanning the frontal, subcortical, and parietal cortex in patients with insomnia disorder ( O'Byrne et al, 2014 , Bagherzadeh-Azbari et al, 2019 ). All these studies sought to infer patterns of abnormal brain functional activity that are common across patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some risk factors are unmodi able, such as age, and others are potentially modi able, such as MDD severity. Though previous studies have explored the negative consequences of sleep disturbances in patients with MDD or cognitive impairment [12,22,23], it is still not known about the role, if any, of sleep disturbances play in the development of cognitive impairment in patients with MDD.…”
Section: Introductionmentioning
confidence: 99%